Hydrogen gas represses the progression of lung cancer via down-regulating CD47. Issue 4 (28th April 2020) - Meng, Jinghong; Liu, Leyuan; Wang, Dongchang; Yan, Zhenfeng; Chen, Gang
Abstract: Hydrogen gas (H2 ) has been identified to play an anti-tumor role in several kinds of cancers, but the molecular mechanisms remain largely unknown. In our previous study, our project group found that H2 could decrease the expression of CD47 in lung cancer A549 cells via the next-generation sequencing, indicating that CD47 might be involved in H2 -mediated lung cancer repression. Therefore, the present study aimed to explore the effects of CD47 on H2 -induced lung cancer repression. Western blotting and real-time PCR (RT-PCR) assays were used to detect the levels of proteins and mRNAs, respectively. Cell proliferation, invasion, migration and apoptosis were detected by using the cell counting kit-8 (CCK-8), Transwell chambers, wound healing and flow cytometry assays, respectively. The results showed that H2 treatment caused decreases in the expression levels of CD47 and cell division control protein 42 (CDC42) in a dose-dependent manner. Up-regulation of CD47 abolished H2 roles in promoting lung cancer cell apoptosis and repressing cell growth, invasion and migration in both A549 and H1975 cell lines. However, knockdown of CD47 enhanced H2 role in lung cancer inhibition. Moreover, we also observed that H2 treatment induced obvious inhibitions in the expression levels of CDC42 and CD47 in mice tumor tissues, as well as reinforced macrophage-mediated phagocytosis in A549 and H1975 cells. In conclusion, the current study reveals that H2 inhibits the progression of lung cancer via down-regulating CD47, which might be a potent method for lung cancer treatment.